Water Transport And Physical Properties Of Sugarcane Bagasse Fibre Reinforced Thermoplastic Potato Starch Biocomposite - Jumaidin, Ridhwan; Adam, Nur Wardah; Azlan, Umar Al-Amani; Hussin, Mohamed Saiful Firdaus; Mohammad Taha, Mastura; Mansor, Muhd Ridzuan; Yob, Mohd Shukri; Ahmad Ilyas, Rushdan (Penerbit Akademia Baru, 2019)
Nowadays, development of bio composites from renewable resources has become great interest as the alternative to replace petroleum-based polymer. Starch is one of the examples of bio polymer that are biodegradable. However, there is limitation on starch usage where starch based polymer has poor mechanical properties and high water sensitivity. Sugarcane waste produced from the extraction of sugarcane juice has potential application to be used as reinforcement material for producing bio-based composites. In this study, Thermoplastic Potato Starch reinforced Sugarcane Fibre (TPPS/SF) composites were developed by using dry mixing and hot press method at 145°C for 1 hour by maintaining the composition of starch and glycerol at ratio 80:20. The sugarcane fibres content ranged from 0 to 15wt.%. This paper presents the results of water transport and physical properties of TPPS/SF composites by using water absorption, thickness swelling, water solubility and moisture content tests. In terms of water transport, the composites show decrease in water absorption capacity of the composites following the addition of sugarcane fibre. Dimensional stability of the composites was increased indicated through the lower thickness swelling reading of the composites. In terms of physical properties, the water solubility of the composites was decreased which indicate improved resistance against water. The moisture content of the composites was decreased gradually following increasing amount of sugarcane fibre in TPSS matrix. Overall, this study shows that incorporation of sugarcane fibre into TPPS has improve the functional properties of this green material.